Basic principles of drug discovery and development - Blass, Benjamin E. (Amsterdam : Elsevier/AP, Academic Press is an imprint of Elsevier, 2015)
Basic Principles of Drug Discovery and Development presents the multifaceted process of identifying a new drug in the modern era, providing comprehensive explanations of enabling technologies such as high throughput screening, structure based drug design, molecular modeling, pharmaceutical profiling, and translational medicine, all areas that have become critical steps in the successful development of marketable therapeutics. The text introduces the fundamental principles of drug discovery and development, also discussing important drug targets by class, in vitro screening methods, medicin.
Drug discovery and development: an overview of modern methods and principles -- The drug discovery process: from ancient times to the present day -- Classical targets in drug discovery -- In vitro screening systems -- Medicinal chemistry -- In vitro ADME and In vivo pharmacokinetics -- Animal models of disease states -- Safety and toxicology -- Basics of clinical trials -- Translational medicine and biomarkers -- Organizational considerations and trends in the pharmaceutical industry -- Intellectual property and patents in drug discovery -- Case studies in drug discovery.
Online resource; title from PDF title page (EBSCO, viewed October 9, 2017)
Includes bibliographical references.
Keywords: Drug development; Drugs -- Design; MEDICAL / Pharmacology; Drug development; Drugs -- Design; Chimie pharmaceutique; Chimie bioorganique; 2; x; Drug Discovery; Drug Evaluation; Electronic books; Electronic book